2000
DOI: 10.1159/000022142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Training on Selected Parameters of Immune Function in Elderly Women

Abstract: Background: Immune function decreases with age, rendering the elderly more susceptible to infection and tumor development. In addition, intense exercise has been shown to decrease immune function in some populations. Few studies have examined the effects of exercise on immune function in the elderly and, to our knowledge, no studies have examined the effects of exercise on a population of active, but nonexercising elderly. Objective: The purpose of this study was to examine the effects of a 10-week endurance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 25 publications
(45 reference statements)
1
36
0
8
Order By: Relevance
“…This problem has been reviewed recently in detail [22] . Several available studies suggest that the immune system function is enhanced in regularly exercising versus sedentary elderly subjects and that an increase in natural killer cell activity and superior T cell function after regular exercise seem to be of utmost importance [2,23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…This problem has been reviewed recently in detail [22] . Several available studies suggest that the immune system function is enhanced in regularly exercising versus sedentary elderly subjects and that an increase in natural killer cell activity and superior T cell function after regular exercise seem to be of utmost importance [2,23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, early studies by Schouten et al (1988) and Karper and Goldfarb (1995) found no conclusive evidence that moderate exercise positively affects humoral immunity, and Nehlsen-Cannarella et al (1990) reported that subjects in their exercise group did not express any significant differences in concentrations of IgA or other serum immunoglobulins. Recently, Fahlman et al (2000) examined the effects of a similar 10 week endurance training programme, similar to that used in the present study, to examine immune function in elderly women. The NK-cell cytotoxicity at rest remained unchanged in the exercise group, while it was significantly decreased in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise interventions of 8 months in frail elderly have also failed to alter the CD4:CD8 T-cell ratio. Similarly, Fahlman et al [11] and Flynn et al [12] reported no change in response to 10 weeks of aerobic or strength exercise training respectively, while McFarlin et al [13] also reported no change in resting CD4+ or CD8+ T-cell numbers in elderly women (aged 65-85 years) in response to 10 weeks' resistance training. Exercise intervention studies of longer duration have also reported no effect.…”
Section: Exercise and The Cd4:cd8 T-cell Ratiomentioning
confidence: 96%